AB0354 In vivo kinematics of three-component mobile-bearing total ankle replacement for rheumatoid arthritis during gait. (23rd January 2014) - Iwamoto, K.; Shi, K.; Tomita, T.; Yamazaki, T.; Futai, K.; Kunugiza, Y.; Yoshikawa, H.; Sugamoto, K.
Abstract : Background: The standard treatment for end-stage arthritis of ankle joint due to rheumatoid arthritis (RA) has been arthrodesis. It is often that patients with RA who require ankle surgery already have destruction of peritalar joints. Since fusion of both the ankle and peritalar joints inevitably results in serious functional problems, total ankle replacement (TAR) that can relieve pain while retaining ankle movement should be useful for patients with RA, especially for those who require peritalar fusion. However, previous studies of conventional TAR have been reported high complication rates and low survivorship, as compared to total knee and hip replacements. This could have primarily been due to excessive contact stress at the relatively small area of ankle joint, and also to the constrained design of the implant. It is expected that recently developed TAR with mobile insert could demonstrate better kinematics than conventional ones, leading to durability of implant as well as maintenance of function. Objectives: The objective of this study was to determine in vivo kinematics of a three-component mobile-bearing TAR in rheumatoid ankle during gait. Methods: We investigated 12ankles in 9 patients with RA implanted with a three-component mobile-bearing TAR (FINE Total Ankle System, Nakashima Medical, Okayama, Japan), which allows not only internal/external rotation but also anteroposterior (AP) translation. Fluoroscopic images were obtained while each patient was asked to perform gait with full weight-bearing on the implanted ankle. Thereafter tibio-talar motion was analyzed by 2D/3D registration technique; a reproduction method of the spatial position of each component in TAR, from single-view fluoroscopic images by use of computer-assisted design models. We evaluated the plantar-/dorsiflexion angle, internal/external rotation angle and AP translation between the components. Results: The average range of tibio-talar motion during the stance phase of gait was 11.0±2.6° (mean ±standard deviation). The average range of internal/external rotation was 3.9±1.3°. However, large intersubject variability resulted in the lack of a uniform pattern of rotational movement. The average amount of AP translation was 1.6±0.7 mm. Conclusions: Mobility of plantar-/dorsiflexion was unexpectedly small during the stance phase of gait, whereas rotation and AP translation was much more insignificant. Also, there was wide inter-subject variability in the original rotational and AP translational position of the components, some of which were regarded as malposition. These results suggest that mobile-bearing TAR could have potential advantage in durability with expectation that it could compensate a certain malposition of the components. References: Nishikawa M, Tomita T, et al. Int Orthop 2004;28:123-126. Shi K, et al. J Foot Ankle Surg 2006;45:316-321. Zuffi S, et al. IEEE Trans Med Imaging 1999;18:981-91. Yamazaki T, et al. IEEE Trans Med Imaging 2004;23:602-612. Komistek RD. Foot Ankle Int 2000;21:343-350. Conti S. Foot Ankle Int 2006;27:980-984. Leszko F. Foot Ankle Int 2008;29:1117-1125. Satoshi Y, et al. J Biomech 2011;44:995-1000. Disclosure of Interest: None Declared